ANALYSIS OF THE DIFFICULTIES OF PRE-SERVICE SOCIAL SCIENCES TEACHER STUDENTS IN MASTERING PEDAGOGICAL COMPETENCE - Muhammad Ilyas Marzuqi; Dhimas Bagus Virgiawan (JURNAL PENDIDIKAN GLASSER, 2025)
The difficulties experienced by pre-service social studies teachers in mastering the pedagogical competencies that are essential for quality education are the urgent background for conducting this study. This study analyzes the difficulties of pre-service social sciences teachers in mastering and designing pedagogical competence, which is the essence of teacher quality. Using a qualitative approach and in-depth interviews with 23 UNESA Social Science Education students, this study identified a significant gap between campus theory and field practice. The main difficulties include adjusting materials and methods to diverse student characteristics, limited media and innovative learning resources, selecting appropriate learning methods, classroom management, and compiling comprehensive assessments. The main causal factors are the lack of direct teaching experience, limited PLP time, lack of practical guidance from lecturers, and self-confidence issues. Although lectures have provided a strong theoretical foundation, this provision is not enough to face classroom reality. These findings emphasize that pedagogical competence is applicative and requires intensive practice. Closer integration between theory and practice, improving the quality, duration of PLP, and contextual guidance are needed. Thus, it is hoped that pre-service social sciences teachers can become adaptive, innovative, and effective educators, contributing to improving the quality of national education.